Effects of LAB inoculant and cellulase on the fermentation quality and chemical composition of forage soybean silage prepared with corn stover. (5th July 2020) - Cheng, Qiming; Li, Ping; Xiao, Bingxue; Yang, Fuyu; Li, Daxu; Ge, Gentu; Jia, Yushan; Bai, Shiqie
Abstract: The objective of the present study was to evaluate the silage quality of forage soybean‐corn stover silage in the south of China. Forage soybean were combined manually with corn stover by ratios of R1 (25:75), R2 (50:50) and R3 (75:25) in fresh weight (FM) and ensiled in bag silos for 60 days at room temperature (20–25°C). All silages were treated without (control) or with lactic acid bacteria (LAB) inoculant (G, Lactobacillus plantarum and Lactobacillus buchneri, 10 5  cfu/g, of FM), cellulase (C, 0.02% of FM) and C + G. R1 silage had appropriate V‐score value with high lactic acid content and low pH value and ammonia‐ N (NH3 ‐N) content, undetectable levels of propionic acid (PA) and butyric acid (BA). C and C + G reduced undesirable microorganisms of aerobic bacteria, yeasts and molds, resulting in improved nutritive value of R2 silage, as indicated by lower neutral detergent fiber and acid detergent fiber contents, and higher crude protein content, in vitro ruminal dry matter digestibility, gross energy and metabolizable energy values as compared to the control. Additives did not improve the quality of R3 silage with high pH value and NH3 ‐N content, BA and PA contents and undesirable microorganism counts. These results confirmed that high‐quality silage produced from mixtures (25:75) of forage soybean and corn stover in the south of China; additives (especially for C + G) could enhance the silage quality of forage soybean‐corn stover (50:50); and high proportion (>75%) of forage soybean was difficult to ensile.